Hubungan Kualitas Pelayanan Kesehatan Terhadap Tingkat Kepuasan Pasien Tuberkulosis di Puskesmas Sebengkok Kota Tarakan: The Relationship Between Health Service Quality and Tuberculosis Patient Satisfaction Levels at the Sebengkok Community Health Center in Tarakan City - Aufia Hafshoh; Umi Setyoningrum (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2026)
Healthcare service quality plays an important role in the success of tuberculosis (TB) treatment. Higher patient satisfaction can improve treatment adherence. However, variations in service quality at primary healthcare facilities may affect patient satisfaction and treatment outcomes, making further investigation necessary. To analyze the relationship between healthcare service quality and the level of patient satisfaction among tuberculosis patients at Sebengkok Public Health Center, Tarakan City. This quantitative study employed a correlational analytic design with a cross-sectional approach conducted in 2026. A total of 66 respondents were included using total sampling. Service quality was categorized as good, moderate, and poor, while patient satisfaction was classified as satisfied, moderately satisfied, and dissatisfied. Data were collected using questionnaires and analyzed with the Chi-Square test. Most respondents perceived service quality as good (42.4%) and reported being satisfied (45.5%). Statistical analysis showed a significant relationship between service quality and patient satisfaction (p = 0.001). Healthcare service quality is significantly associated with patient satisfaction among TB patients. Improving service quality is essential to support successful treatment outcomes. ABSTRAK Kualitas pelayanan kesehatan berperan penting dalam keberhasilan pengobatan tuberkulosis (TB). Kepuasan pasien yang tinggi dapat meningkatkan kepatuhan pengobatan. Namun, variasi kualitas pelayanan di fasilitas kesehatan tingkat pertama masih berpotensi mempengaruhi kepuasan pasien dan keberhasilan terapi, sehingga perlu dikaji lebih lanjut. Menganalisis hubungan antara kualitas pelayanan kesehatan dengan tingkat kepuasan pasien tuberkulosis di Puskesmas Sebengkok Kota Tarakan. Penelitian kuantitatif dengan desain analitik korelasional dan pendekatan cross-sectional tahun 2026. Sampel berjumlah 66 responden menggunakan teknik total sampling. Kualitas pelayanan dikategorikan menjadi baik, cukup, dan kurang, sedangkan kepuasan pasien menjadi puas, cukup puas, dan kurang puas. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan uji Chi-Square. Sebagian besar responden menilai kualitas pelayanan dalam kategori baik (42,4%) dan merasa puas (45,5%). Analisis menunjukkan hubungan signifikan antara kualitas pelayanan dan kepuasan pasien (p = 0,001). Kualitas pelayanan kesehatan berhubungan signifikan dengan tingkat kepuasan pasien TB, sehingga peningkatan mutu pelayanan menjadi faktor penting dalam mendukung keberhasilan pengobatan.